Turbulent Mixing and the Formation of an Intermediate Nepheloid Layer Above the Siberian Continental Shelf Break. Issue 9 (8th May 2021) - Schulz, Kirstin; Büttner, Stefan; Rogge, Andreas; Janout, Markus; Hölemann, Jens; Rippeth, Tom P.
Abstract: Intermediate nepheloid layers (INLs) form important pathways for the cross‐slope transport and vertical export of particulate matter, including carbon. While intermediate maxima in particle settling fluxes have been reported in the Eurasian Basin of the Arctic Ocean, direct observations of turbid INLs above the continental slope are still lacking. In this study, we provide the first direct evidence of an INL, coinciding with enhanced mid‐water turbulent dissipation rates, over the Laptev Sea continental slope in summer 2018. Current velocity data show a period of enhanced downslope flow with depressed isopcynals, suggesting that the enhanced turbulent dissipation is probably the consequence of the presence of an unsteady lee wave. Similar events occur mostly during ice free periods, suggesting an increasing frequency of episodic cross‐slope particle transport in the future. The discovery of the INL and the episodic generation mechanism provide new insights into particle transport dynamics in this rapidly changing environment. Plain Language Summary: In the Arctic Ocean deep basins, only a tiny fraction of the algae that grows in the surface layer sinks down to the sea floor. Most of the particles reaching the sea floor originate from the shallower regions closer to the coast. These particles have already settled on the sea floor once, and originate from rivers or algae that grew, died and sank down in shallow regions. Later, these particles are lifted off the ground again by strong turbulent motions and transported toward deeper regions in the middle of the water column. These lift‐off and transport events happen only occasionally, and have not been directly observed in the Eurasian part of the Arctic Ocean yet. Also, we present a new mechanism for the creation of turbulence, which is necessary to lift particles off the sea floor. This mechanism happens mostly during the summer season, when less sea ice is present. Based on this seasonality, it is likely that sediment transport events will become more frequent in the future, when the Arctic sea ice is further declining. Key Points: First direct observation of an intermediate nepheloid layer in the Eurasian part of the Arctic Ocean Coinciding strong midwater turbulence is likely caused by a down‐slope current displacing isopycnals Similar downslope flow events exhibit a strong seasonality toward the ice free season